Disintegration of anterior thalamic radiation fibers in cerebrovascular disease subjects with periventricular white matter hyperintensities leads to lower executive function performance. (December 2021) - Haddad, Seyyed Mohammad Hassan; Scott, Christopher J.M.; Ozzoude, Miracle; Holmes, Melissa F.; Arnott, Stephen R.; Nanayakkara, Nuwan D.; Kwan, Donna; Tan, Brian; Casaubon, Leanne; Mandzia, Jennifer; Sahlas, Demetrios J.; Saposnik, Gustavo; et al.
Abstract: Background: White matter hyperintensities (WMH) are more prevalent in elder adults and those typically located in periventricular areas are known as periventricular WMHs (pWMH). Recent studies link WMHs to hypoperfusion and ischemic injuries arising from diverse cerebrovascular diseases (CVDs). Previous studies have reported strong associations between WMH burden and disintegration of normal‐appearing white matter (WM) and WM pathways evaluated using diffusion tensor imaging (DTI). This WM deterioration may be the underlying cause of cognitive dysfunction in people with WMHs. The purpose of this study is to identify major WM tracts in which there is evidence of microstructure damage associated with pWMH severity to determine whether this damage is associated with cognitive decline. Method: Association between pWMH volume and fractional anisotropy (FA) in 18 major WM tracts in 100 CVD subjects (aged 55‐84 years, 29% female, evidenced by an ischemic stroke event documented by MRI or CT, with a modified Rankin score 0‐3) from the Ontario Neurodegenerative Disease Research Initiative was examined using linear regression. DTI (30 directions, b=1000 s/mm 2 ) was acquired on eight 3T MRI scanners. Mean FA in 18 WM tracts was quantified using TRACULA in FreeSurfer in each subject. Volumes of pWMHs were obtained by semi‐automated segmentation of T1 ‐weighted images in each subject. Cognitive assessments were completed as part of ONDRI. Associations between cognitive scores and FA in tracts that significantly correlated with pWMH severity were also examined. Result: Linear regression (adjusted by age and sex) detected significant correlation between FA in right anterior thalamic radiation (ATR) (Fig. 1) and pWMH volume after Bonferroni correction ( p ‐value=0.002, r=‐0.356) (Fig. 2). No other significant associations were identified. Since right ATR is part of fronto‐striato‐thalamic circuit contributing to executive function, FA in ATR predicted association with Trail Making Test‐Part B (adjusted by age, sex, and education) and a signhificant correlation was identified ( p ‐value=0.006, r=‐0.256) (Fig. 3). Conclusion: ATR disintegration was associated with pWMH severity in participants with CVD and with executive function. This study suggests that tissue microstructure deterioration in ATR measured by DTI may contribute to decline in executive function in CVD patients with pWMHs.